SISTEM PENGETAHUAN PESANTREN SEBAGAI MODEL EPISTEMOLOGI ISLAM NUSANTARA: ANALISIS LITERATUR - Rasti Astuti Laisaan; Muhammad Husni (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This research aims to examine and formulate the knowledge system of Islamic boarding schools (pesantren) as a model of Nusantara Islamic epistemology relevant to the development of contemporary Islamic education. This research employs a literature review method, examining recent scholarly works on Islamic boarding schools, classical Islamic epistemology, and modern Islamic educational theory. Through a critical analysis of this literature, the research identifies that the knowledge system of Islamic boarding schools is constructed through a combination of the scholarly authority of the kiai (Islamic scholars), the sanad tradition, the study of yellow books (kitab kuning), the practice of bahtsul mas?'il (religious discourse), and the integration of three epistemological approaches: bayani (textual), burhani (rational-empirical), and irfani (spiritual-intuitive). These findings demonstrate that Islamic boarding schools function not only as centers for the transmission of classical Islamic knowledge but also as institutions capable of producing new knowledge products contextualized to the socio-religious dynamics of Indonesian society. The results confirm that Islamic boarding school epistemology makes a significant contribution to the construction of an Nusantara Islamic epistemology characterized by moderation, local wisdom, and adaptability to modernity. Theoretically, this research strengthens the position of Islamic boarding schools as epistemic sources distinct from Middle Eastern models of scholarship and modern-secular educational paradigms. Practically, this epistemological model can serve as a basis for developing a more relevant, integrative Islamic education curriculum oriented toward developing spiritual character and 21st-century competencies.